The Practice Of Programme-Based Budgeting: A Case Study Of A Mosque In Surabaya - Hari Santoso Wibowo; Muh Syahril Sidik Ibrahim; Ibnu Nafi Ahmad; Muhammad Fuzail (PT Agung Media Publisher, 2024)
This research article delves into the budget planning process at the Ar-Rahmah Mosque in Surabaya, employing a qualitative case study approach. Data was gathered through interviews with key mosque administrators, including the director, treasurer, and department heads. The findings reveal that the Ar-Rahmah Mosque adopts a bottom-up, program-based budgeting method. This process encompasses the preparation and ratification stages of the budget, with careful consideration of revenue and expense forecasting, as well as budget approval. The study highlights that this approach facilitates a more inclusive and participatory budgeting process, ensuring that the financial plan aligns closely with the mosque's various programs and activities. The implications of this research are particularly significant for other mosques and nonprofit organizations looking to enhance their budget planning strategies. By adopting a program-based budgeting approach, these organizations can potentially achieve greater financial efficiency and transparency. This case study of the Ar-Rahmah Mosque provides a valuable model for effective budget planning that can be emulated by similar institutions aiming to improve their financial management practices.